Inventarisasi Jenis Burung di Areal Bekas Tambang Batubara PT Pilar Putra Sejati Kelurahan Loa Bakung Kecamatan Sungai Kunjang Samarinda - M. Masrudy; M. Fadjeri; Emy Malaysia; Dwinita Aquastini (Poltanesa, 2021)
The purpose of this study was to determine the presence of bird species in the area of ​​the former coal mine of PT. Pilar Putra Sejati, Loa Bakung Village, Sungai Kunjang District, Samarinda.This research has been carried out for approximately three months starting from May 2021 to September 2021. The method used for observing birds is a direct method using traps or traps in the form of fog nets and traps or snares, where observations are made at six points , as follows; three points on the edge of the dug hole and three points located on trees frequented by birds. At each point, observations were held in the morning at 06.00-08.00 and in the afternoon at 16.00-18.00 WITA.The results of observations at the research location found as many as 9 species of birds from 6 families. Bird species during the study were Lonchura punctulata (Ploceidae family), Passer montanus (Ploceidae family), Streptopelia chinensis (Colombidae family), Giopelia striata (Colombidae family), Arborophila charltonii (Phasianidae family), Phynonotus aurigaster (nis family), Aenicurus family Rallidae), Acridotheres javanicus (family Sturnidae), and Lonchura fuscans (family Ploceidae).